A characterization of the patients of UPCD and the factors that would attract and retain them - Aquino, Bernicella
In this study it is aimed to know the reasons why patients prefer UPCD for treatment, to understand and gain insight on the attitudes and expectations of patients in the school clinic and to gather information that would be of assistance to the administration in improving presently existing programs so as to attract and retain more patients. A 26-item questionnaire of the patients of the UPCD and the factors that would attract and retain them. It was gathered that the reasonable cost of treatment is the primary inducement to select UPCD and in the quality of the dental work and the use of modern techniques. The typical patient sees the clinicians concentrate on her work while displaying concern over her feelings and the faculty strictly and carefully supervises her.